Financial development beyond the formal financial market - Lin Shao (Bank of Canada, 2018)
This paper studies the effects of financial development, taking into account both formal and informal financing. Using cross-country firm-level data, we document that informal financing is utilized more by rich countries than poor countries. To account for this empirical pattern, we build a model in which the supply of informal financing increases with financial development, while the demand for informal financing declines with it. The model generates a hump-shaped relationship between the incidence of informal financing and GDP per capita. Our analysis shows that, at the early stage of economic development, the output loss from financial frictions is reinforced by the low supply of informal financing. Informal financing contributes more to the aggregate output of the richest countries than to that of the poorer countries in our sample.
Keywords: E44; O17; O47; 330; Productivity; Financial markets; Firm dynamics